High on-treatment platelet reactivity and outcome in elderly with non ST-segment elevation acute coronary syndrome - Insight from the GEPRESS study. (15th May 2018) - De Rosa, Roberta; Palmerini, Tullio; De Servi, Stefano; Belmonte, Marta; Crimi, Gabriele; Cornara, Stefano; Calabrò, Paolo; Cattaneo, Marco; Maffeo, Diego; Toso, Anna; Bartorelli, Antonio; Palmieri, Cataldo; et al.
Abstract: Background: Elderly treated with dual antiplatelet therapy after percutaneous coronary intervention (PCI) represent a challenging population because of increased risk of both ischemic and bleeding events. We aimed to investigate the association between high on-treatment platelet reactivity (HPR) and long-term outcome in elderly with non-ST-elevated acute coronary syndromes (NSTE-ACS) undergoing PCI. Methods: Platelet reactivity was measured by vasodilator-stimulated phosphoprotein (VASP) assay at three time-points (baseline, discharge, 1 month after PCI) in 1053 NSTE-ACS patients (311 elderly) treated with clopidogrel. Major adverse cardiac events (MACE) were assessed up to 1 year-follow-up. Results: Elderly with HPR at discharge showed a significantly higher incidence of overall MACE (13 vs 4%, p = .006), cardiac death (6 vs 0.7%, p = .020), myocardial infarction (MI, 12 vs 4%, p = .031) and a trend for higher stent-thrombosis (5 vs 0.7%, p = .068). Similarly, elderly with 1-month-HPR showed between 1 month and 1 year significantly higher incidence of MACE (10 vs 4%, p = .012), cardiac death (6 vs 0.7%, p = .019) and composite cardiac death/MI (11 vs 4%, p = .014). Up to 1 year, elderly with HPR showed a 4-fold increased risk of MACE compared to both elderly without HPR (for discharge-HPR: p = .005; for 1-month-HPR: p = .01) and non-elderly with HPR (for discharge-HPR: p < .001; for 1-month-HPR: p < .0001). At multivariable analysis, HPR could independently predict 1-year-MACE in elderly (for discharge-HPR: HR = 3.191, CI: 1.373–7.417, p = .007; for 1-month-HPR: HR = 3.542, CI: 1.373–9.137, p = .009). Conclusions: In elderly with NSTE-ACS undergoing PCI and treated with clopidogrel, HPR was independently associated with an increased risk of MACE up to 1 year. Highlights: We measured on-therapy platelet reactivity (PR) in NSTE-ACS patients treated by PCI. High on-therapy PR was independently associated with bad outcome in the elderly. The Syntax score did not independently predict adverse outcome in the elderly.